Determination of dislocation density in GaN layers using KOH defect MOVPE grown etching - Wellmann, Peter; Sakwe, Aloysius; Oehlschläger, Felix; Hoffmann, Veit; Zeimer, Ute; Knauer, Arne (Journal of Crystal Growth, 2008)
We report on molten KOH-based defect etching of GaN epitaxial layers for the quantitative determination of the dislocation density. Etching process parameters were established at 450 degrees C that are suitable to reveal threading edge and threading screw dislocations at the same time and, hence, allow for the quantitative determination of the total dislocation density in the metal organic vapor-phase epitaxy (MOVPE) grown GaN layers. The determined dislocation numbers in the 10(8)cm(-2) range are correlated (i) with the full-width half-maximum of rocking curves of the (3 0 (2) over bar) reflection and (ii) dark spots observed by cathodoluminescence of the etched GaN surfaces. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Defect etching; GaN; KOH

Determination of material inhomogeneities in CuIn(Se,S)(2) solar cell materials by high resolution cathodoluminescence topography - Oehlschläger, Felix; Müller, Julian; Künecke, Ulrike; Hoelzing, Astrid; Schurr, Roland; Hock, Rainer; Wellmann, Peter (Energy Procedia, 2010)
CIS based polycrystalline semiconductors are used for thin film solar cells in laboratory and industry. Nevertheless, even for highly efficient absorbers from different growth techniques, these films are reported to contain inhomogeneities from nanometer to millimeter scale. In this paper we have analyzed inhomogeneities on a sub-mu m scale of CuIn(Se,S)(2) solar cell absorber materials processed by annealing of elemental layer precursors using high spatial resolution cathodoluminescence mapping. The measurements were carried out in a scanning electron microscope which has cathodoluminescence (CL) and energy dispersive x-ray fluorescence (EDX) capabilities to study materials composition. Cathodoluminescence from CuIn(Se,S)(2) at energies around 0.9 eV to 1.2 eV was detected by a spectrometer with a cooled InGaAs photo diode array. For better luminescence signals, the samples were cooled down to 80K (liquid nitrogen). From the energetic position of the cathodoluminescence peaks we have deduced the varying CuIn(Se,S)(2) materials composition. EDX measurements were carried out to verify the CL. (C) 2010 Published by Elsevier L
Keywords: Cathodoluminescence; CL; Energy dispersive x-ray; EDX; thin film; absorber; CuIn(S; Se); topography; mapping

Differential calorimetry study of the initial stage of the sulphurisation process of CuInSe2 solar cell materials - Tang, K.; Künecke, Ulrike; Oehlschläger, Felix; Hölzing, Astrid; Schurr, R.; Hock, Rainer; Wellmann, Peter (Solar Energy Materials and Solar Cells, 2010)
Sulphurisation of CuInSe2 solar cell absorber materials is of particular interest for band gap engineering by means of compositional grading. We studied the chalcopyrite formation process of Cu-In-S-Se stacks with varying Se to S ratio from 100% Se (0% S) down to 0% Se (100% 5). Differential calorimetry (DSC) was applied as a fundamental characterization tool to track the crystal phase formation process. To verify the evolution of various crystallographic phases, DSC measurements were supplemented by temperature dependent in-situ X-ray diffraction (XRD) experiments of equivalent thin film compositions. For a S content of 25% the system is governed by sulphurisation of Cu and In, with the ternary phase CuIn5(S,Se)(8) and the binary phase Cu-2(S,Se) playing major roles in the chalcopyrite formation process. It is found that the chalcopyrite formation moves to higher temperatures if the S content is increased. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: CuIn(S; Se)2; Chalcopyrite; Thin films; Sequential processing; Thermal analys

P- and n-type Doping in SiC Sublimation Epitaxy Using Highly Doped Substrates - Hens, Philip; Syvaejaervi, Mikael; Oehlschläger, Felix; Wellmann, Peter; Yakimova, Rositza (Materials Science Forum, 2009)
The co-doping of nitrogen and aluminum has been Studied in the sublimation epitaxy growth process. It is shown that the doping may be tuned from n-type to p-type by, effect of substrate, doping, growth face and volume of the growth crucible. The co-doped layers show a nearly ideal I-V characteristic and luminescence at room temperatur
Keywords: Compensation; Doping; Growth; Sublimation

Photoluminescence-topography of the p-type Doped SiC Wafers for Determination of Doping Inhomogeneity - Oehlschläger, Felix; Juillaguet, Sandrine; Peyre, Herve; Calmassel, Jean; Wellmann, Peter (Materials Science Forum, 2009)
Photoluminescence(PL)-topography is a powerful method to determine the charge carrier concentration of SiC-wafers. The following, work describes the development of a PL-topography method for the determination of charge carrier distribution in p-type SiC and shows the correlation of PL-Intensity and charge carrier concentration. With this setup it is possible to characterize wafers up to a size of 2" at room- and low temperature in a non-destructive wa
Keywords: Absorption Measurements; Determination of Doping Inhomogeneity; Mapping; Photoluminescence-Topography; PL